2010
DOI: 10.1007/s11604-010-0494-1
|View full text |Cite
|
Sign up to set email alerts
|

Pneumothorax and idiopathic pulmonary fibrosis

Abstract: Pneumothorax in IPF patients is associated with lower VC and rapid deterioration of CT findings. The findings suggest that pneumothorax is a complication of advanced IPF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
18
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 21 publications
4
18
3
Order By: Relevance
“…Thus, lines of directly adjacent stiff fibrotic tissue and pliable native lung parenchyma exist, along which considerable tension is likely to occur throughout the ventilatory cycle, leading to pleural tearing and pneumothorax. Although speculative, this appears to be corroborated by previous studies showing an increased risk of pneumothorax in idiopathic pulmonary fibrosis (in which discontinuous subpleural fibrosis is also common), 14 and higher risk of recurrent pneumothorax in pulmonary fibrosis. 15 Histomorphologically, the so-called 'apical cap', which is a localised lesion of subpleural fibrosis that predominantly occurs in the apices of the upper lobes, enters the differential diagnosis of pleuroparenchymal fibroelastosis.…”
Section: Discussionsupporting
confidence: 64%
“…Thus, lines of directly adjacent stiff fibrotic tissue and pliable native lung parenchyma exist, along which considerable tension is likely to occur throughout the ventilatory cycle, leading to pleural tearing and pneumothorax. Although speculative, this appears to be corroborated by previous studies showing an increased risk of pneumothorax in idiopathic pulmonary fibrosis (in which discontinuous subpleural fibrosis is also common), 14 and higher risk of recurrent pneumothorax in pulmonary fibrosis. 15 Histomorphologically, the so-called 'apical cap', which is a localised lesion of subpleural fibrosis that predominantly occurs in the apices of the upper lobes, enters the differential diagnosis of pleuroparenchymal fibroelastosis.…”
Section: Discussionsupporting
confidence: 64%
“…It can hypothetically be attributed to the rupture of subpleural areas of honeycombing cysts. In contrast, the frequent coexistence of pulmonary fibrosis and emphysema does not seem to be a causative factor, since this and an earlier study were not able to demonstrate a significantly greater prevalence of emphysematous changes in IPF patients suffering from SSP. Nor does the potential miscategorization of pleuroparenchymal fibroelastosis as IPF seem to be a convincing explanation.…”
contrasting
confidence: 83%
“…Spontaneous pneumothorax can develop anytime during the clinical course in patients with IPF (Fig. ), which could explain the variance in the incidence of pneumothorax reported in former studies …”
Section: Discussionmentioning
confidence: 94%
“…Our results determining the cumulative incidence of pneumothorax indicated that patients with IPF have a continuous risk of developing pneumothorax during their clinical course. One study reported that occurrence of pneumothorax in patients with IPF was 6.4%, and the other reported that was 30.4% . Spontaneous pneumothorax can develop anytime during the clinical course in patients with IPF (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation